2011
DOI: 10.1098/rspb.2011.1718
|View full text |Cite
|
Sign up to set email alerts
|

A shared chemical basis of avian host–parasite egg colour mimicry

Abstract: Avian brood parasites lay their eggs in other birds' nests and impose considerable fitness costs on their hosts. Historically and scientifically, the best studied example of circumventing host defences is the mimicry of host eggshell colour by the common cuckoo (Cuculus canorus). Yet the chemical basis of eggshell colour similarity, which impacts hosts' tolerance towards parasitic eggs, remains unknown. We tested the alternative scenarios that (i) cuckoos replicate host egg pigment chemistry, or (ii) cuckoos u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 68 publications
(130 reference statements)
1
64
0
Order By: Relevance
“…The receptor noise-limited (RNL) color discrimination model [4] has been widely used to estimate avian color discrimination capabilities [37], [47], [48], and [49]. The model calculates the difference between points (ΔS) within a theoretical color space as defined by the quantum catch of each receptor type within the retina of the species of interest.…”
Section: A3 Appendixmentioning
confidence: 99%
“…The receptor noise-limited (RNL) color discrimination model [4] has been widely used to estimate avian color discrimination capabilities [37], [47], [48], and [49]. The model calculates the difference between points (ΔS) within a theoretical color space as defined by the quantum catch of each receptor type within the retina of the species of interest.…”
Section: A3 Appendixmentioning
confidence: 99%
“…Within the above-outlined subset of hosts, the most common host species is the pied flycatcher Ficedula hypoleuca with 59 cases of parasitism, almost exclusively from Finland from the first half of the 20th century (Stokke et al, unpublished data). Although cuckoo eggs found in pied flycatcher nests are blue when perceived with human sight, such as those of the sympatric host race of the redstart, cuckoo eggs are in fact spectrally, perceptually, and chemically more similar to redstart than flycatcher eggs (Igic et al 2012). This and the absence of rejection of even highly nonmimetic eggs by the pied flycatcher (von Haartman 1976;Davies and Brooke 1989) suggest that the recent reduction in the frequency of cuckoo parasitism in the pied flycatcher is caused by a large increase in the number of nest boxes for flycatchers that do not allow the cuckoo to lay its egg .…”
Section: Introductionmentioning
confidence: 99%
“…Prior perceptual modelling has revealed that the consistently low chromatic contrasts between the background colours of host and parasite eggs render most cuckoo eggs visually indistinguishable from the host's own eggs (Stoddard and Stevens 2011 ;Igic et al 2012 ;Hauber et al 2015 ). Yet, these hosts still reject about one-third of naturally laid parasite eggs in the Hungarian population (Moskát et al 2009 ), likely by identifying poorly mimetic foreign eggs through both maculation (Moskát et al 2010 ) and coloration (Bán et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies assess chromatic reflectance and/or pattern data to characterize how the tetrachromatic avian visual system assesses the foreign eggshell's appearance (Avilés et al 2010 ;Stoddard and Stevens 2011 ;Hanley et al 2013 ;Igic et al 2012 ;Poláček et al 2013 ;Stoddard et al 2014 ), and have repeatedly confirmed long-standing conclusions that foreign eggs are rejected more often when they are perceived as more dissimilar to the hosts' own eggs (Cassey et al 2008 ;Spottiswoode and Stevens 2010 ;Stevens et al 2013 ;Croston and Hauber 2014 ;Hauber et al 2015 ; Fig. 1 ).…”
Section: Aq4mentioning
confidence: 98%
See 1 more Smart Citation